A kind of anti-aging rock asphalt composite modified asphalt and preparation method thereof

Porous modified silicone rubber and zirconium disilicon powder were prepared through the composite ratio of Iranian rock asphalt, asphalt modification additives, aromatic oil substances and plasticizers, which solved the problem of poor crack resistance of Iranian rock asphalt modified asphalt in low temperatures. , achieving improvements in high and low temperature performance and anti-aging performance.

CN118496682BActive Publication Date: 2025-01-17GUANGDONG ROAD DOCTOR TRANSPORTATION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410423500.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-09
Publication Date
2025-01-17
Estimated Expiration
2044-04-09

AI Technical Summary

Technical Problem

The low-temperature crack resistance of Iranian rock asphalt modified asphalt has limited its promotion and application, and traditional improvement methods have affected other properties of asphalt, such as strength and anti-aging properties.

Method used

Using the composite ratio of Iranian rock asphalt, asphalt modification additives, aromatic oil substances and plasticizers, porous modified silicone rubber is prepared through specific preparation methods, combined with zirconium disilide powder, to improve the high and low temperature performance and anti-aging of asphalt performance.

Benefits of technology

It significantly improves the high and low temperature performance and anti-aging properties of Iranian rock asphalt modified asphalt, enhances its crack resistance, and maintains other excellent properties of asphalt.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004783190790000091
    Figure BDA0004783190790000091
Patent Text Reader

Abstract

The present invention relates to an anti-aging rock asphalt composite modified asphalt and a preparation method thereof, wherein the rock asphalt composite modified asphalt is calculated by weight, including: 100 parts of base asphalt, 5-20 parts of Iranian rock asphalt, 8-15 parts of asphalt modification additives, 2-4 parts of aromatic oil substances and 1-3 parts of plasticizers; wherein the base asphalt is any one of 70# and 90# base asphalt, and the asphalt modification additive is modified silicone rubber. The present invention prepares an Iranian rock asphalt composite modified asphalt with anti-aging property, and in addition to the base asphalt, Iranian rock asphalt and asphalt modification additives are added to the raw materials, and after composite use, the high and low temperature performance of the Iranian rock asphalt modified asphalt is improved on the one hand, and its anti-aging property is improved on the other hand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of asphalt, and in particular to an anti-aging rock asphalt composite modified asphalt and a preparation method thereof. Background Art

[0002] At present, rock asphalt is a modifier that has been maturely studied and applied in the field of asphalt materials. It has stable properties, huge reserves, and very good application prospects, and has attracted extensive attention from scholars at home and abroad. Common rock asphalts include North American rock asphalt, Buton rock asphalt, European rock asphalt, Qingchuan rock asphalt, and Iranian rock asphalt.

[0003] Iranian rock asphalt (IRA) is a common natural rock asphalt, named after its formation in Iran in the Middle East. It is a black solid in appearance. Adding it to asphalt as a modifier has the following advantages: (1) The softening point of Iranian rock asphalt can reach 160-175°C. After adding Iranian rock asphalt, the softening point of asphalt will be significantly improved, the high temperature stability of asphalt mixture will be greatly improved, and the high temperature performance of asphalt pavement can be significantly improved; (2) Iranian rock asphalt has good compatibility with petroleum asphalt, good storage stability, simple preparation process, and convenient storage; (3) Iranian rock asphalt can better withstand the erosion of the natural environment and has good antioxidant properties. The addition of Iranian rock asphalt has a significant effect on improving the anti-aging performance of asphalt and a certain degree of improvement in the durability of asphalt pavement, extending the service life of asphalt pavement to a certain extent. However, the modified asphalt prepared by its modification has poor low-temperature crack resistance, which seriously limits its promotion and application.

[0004] In response to the problem of poor low-temperature crack resistance of rock asphalt modified asphalt, patents CN106189291 and CN110079104 respectively improve the low-temperature performance of rock asphalt modified asphalt by adding a large amount of thermoplastic elastomers and polymers such as styrene-butadiene rubber. Although the low-temperature resistance is improved, it affects other properties of the asphalt, such as weakened strength and poor anti-aging performance.

[0005] Therefore, the Iranian rock asphalt composite modified asphalt with anti-aging properties proposed in the present invention is used to prepare rock asphalt modified asphalt with high strength, excellent anti-aging and high and low temperature properties. Summary of the invention

[0006] In view of the problems existing in the prior art, the object of the present invention is to provide an anti-aging composite modified asphalt and a preparation method thereof.

[0007] The purpose of the present invention is achieved by the following technical solutions:

[0008] In a first aspect, the present invention provides an anti-aging rock asphalt composite modified asphalt, which comprises, by weight, 100 parts of base asphalt, 5-20 parts of Iranian rock asphalt, 8-15 parts of asphalt modification additives, 2-4 parts of aromatic oil substances and 1-3 parts of plasticizer.

[0009] Preferably, the base asphalt is any one of 70# and 90# base asphalt.

[0010] Preferably, the asphalt content of the Iranian rock asphalt is ≥80wt%, the ash content is ≤20wt%, the water content is ≤1wt%, the solubility of trichloroethylene is ≥84wt%, and the density is 0.90-0.97g / cm 3 (25℃), black in color, and 100 mesh in particle size.

[0011] Preferably, the aromatic oil substance is furfural extracted oil with a density of 1.02 g / cm 3 (15.6℃), kinematic viscosity is 42.6mm 2 / s (100℃), the total aromatic content is 82.8wt%.

[0012] Preferably, the plasticizer is any one of dioctyl phthalate (DOP), dioctyl maleate (DOM), tri-n-butyl citrate (TBC) and composite vegetable fatty acid (T60).

[0013] Preferably, the asphalt modification additive is modified silicone rubber.

[0014] Preferably, the preparation method of the asphalt modification additive comprises:

[0015] S1. Treatment of zirconium disilicide:

[0016] Weighing zirconium disilicide nanopowder and γ-glycidyloxypropyltrimethoxysilane, mixing them into anhydrous ethanol, ultrasonicating them at room temperature until they are uniform, then dropping acetic acid to adjust the pH to 4-5, raising the temperature to 40-50° C., keeping the temperature and stirring for 8-16 hours, after the reaction is completed, filtering out the powder, washing with water for at least three times, and drying at 80° C. to obtain epoxidized zirconium disilicide powder;

[0017] S2. Preparation of silicone rubber:

[0018] Vinyl silicone oil, 1-ethynyl-1-cyclohexanol, hydrogenated silicone oil and Karstedt catalyst are added to the mixing device in sequence, and after a short period of high-speed stirring, i.e., stirring at a speed of 700-900 rpm for 2-3 minutes, ammonium carbonate powder is added, and then stirred at a speed of 1000-1200 rpm for 3-5 minutes, placed in a mold and allowed to stand for 10 minutes, and then placed in a condition of 60-80°C for 20 minutes, and then placed in a condition of 130-140°C for 30 minutes, and then naturally cooled, crushed and sieved to obtain porous silicone rubber particles;

[0019] S3, Silicone rubber pretreatment:

[0020] The porous silicone rubber particles are immersed in an ethanol solution, and after being completely soaked, γ-aminopropyltriethoxysilane is added, and the mixture is stirred at room temperature for 3-6 hours, and then filtered, washed with water for at least three times, and dried at 80° C. to obtain a silicone rubber pretreatment product;

[0021] S4. Preparation of modified silicone rubber:

[0022] The silicone rubber pretreatment product and the epoxidized zirconium disilicide powder are mixed into toluene, ultrasonically homogenized, swelled for half an hour, then heated to 60-70°C, refluxed and stirred for 3-5 hours, filtered and dried to obtain the modified silicone rubber.

[0023] Preferably, in S1, the particle size of the zirconium disilicide nanopowder is 200-300 nm, and the mass ratio of the zirconium disilicide nanopowder, γ-glycidyloxypropyltrimethoxysilane and anhydrous ethanol is 1:0.25-0.35:10-20.

[0024] Preferably, in S2, the vinyl silicone oil is RH-Vi302 or RH-Vi303, and the hydrogen-containing silicone oil is MHX-1107.

[0025] Preferably, in S2, the mass ratio of vinyl silicone oil, 1-ethynyl-1-cyclohexanol, hydrogen-containing silicone oil and Karstedt catalyst is 21.1-27.9:1.53-2.03:0.4-0.6:0.96-1.27.

[0026] Preferably, in S2, the particle size of the ammonium carbonate powder is 5±0.1 μm, and the added amount is 3%-8% of the mass of the vinyl silicone oil.

[0027] Preferably, in S2, the sieving is through a 50-mesh sieve.

[0028] Preferably, in S3, the mass fraction of the ethanol solution is 50%, and the mass ratio of γ-aminopropyltriethoxysilane, porous silicone rubber particles and the ethanol solution is 2.5-4.5:10-15:100.

[0029] Preferably, in S4, the mass ratio of the silicone rubber pretreatment material, the epoxidized zirconium disilicide powder and toluene is 1:0.12-0.24:10-20.

[0030] In a second aspect, the present invention provides a method for preparing an anti-aging rock asphalt composite modified asphalt, the process comprising screening, pretreatment, stirring and development of Iranian rock asphalt, comprising the following steps:

[0031] Step 1: crush the Iranian rock asphalt and sieve it with a 50-mesh sieve;

[0032] Step 2: Weigh the aromatic oil and plasticizer according to weight, stir evenly, and then divide the mixture into group A and group B according to a weight ratio of 3:1;

[0033] Step 3: Weigh the Iranian rock asphalt and asphalt modification additive according to the mass ratio, mix them with Group A in Step 2, stir them quickly and evenly, and then put them into an oven for curing;

[0034] Step 4: Place the base asphalt in an oven, heat it to flow, weigh the asphalt according to the mass ratio, and perform high-speed shearing with the cured Iranian rock asphalt mixture;

[0035] Step 5: Replace the high-speed shearing equipment in step 4 with a mechanical stirring equipment, add group B in step 2 into the mixture obtained in step 4, and stir and develop it. After the development is completed, a composite modified asphalt can be obtained.

[0036] The beneficial effects of the present invention are:

[0037] 1. The present invention prepares an Iranian rock asphalt composite modified asphalt with anti-aging properties. In addition to the base asphalt, Iranian rock asphalt and asphalt modification additives are added to the raw materials. After composite use, on the one hand, the high and low temperature performance of the Iranian rock asphalt modified asphalt is improved, and on the other hand, its anti-aging performance is improved.

[0038] 2. The asphalt modification additive used in the present invention is a modified silicone rubber material. After a porous silicone rubber is prepared in a unique way, the zirconium disilicide powder is combined with the epoxy-amino group to fix the zirconium disilicide nanopowder inside the pores of the silicone rubber. The modified silicone rubber finally prepared is used in asphalt. Compared with traditional silicone rubber, its anti-aging and oil resistance are greatly enhanced.

[0039] 3. In the process of preparing modified silicone rubber of the present invention, the silicone rubber is prepared by using vinyl silicone oil and hydrogen silicone oil as rubber raw materials, under the conditions of 1-ethynyl-1-cyclohexanol as an inhibitor and Karstedt platinum catalyst as a catalyst, and ammonium carbonate is added in the preparation process, which will gradually decompose and produce gas during the subsequent heating and curing process, thereby causing the silicone rubber to produce a large number of pores. The heating process adopts a two-stage heating process to ensure that the pores are uniformly generated and to make the silicone rubber cure more uniformly.

[0040] 4. The porous silicone rubber prepared by the present invention has a certain adsorption capacity. After being treated with aminosilane, the adsorption capacity is enhanced. After swelling with aromatic hydrocarbons, the zirconium disilicide powder can be more easily adsorbed into the pores. The zirconium disilicide powder is fixed in the pores of the silicone rubber by combining the epoxy group with the amino group. Zirconium disilicide has the advantages of high thermal stability, good oxidation resistance, high hardness and good chemical stability. Compared with direct compounding in silicone rubber, the porous cross-linking method of the present invention can ensure the advantages of silicone rubber while increasing its anti-aging performance. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is described below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not exclude the existence of other method steps before and after the combination step or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to limit the scope of the present invention. The change or adjustment of the relative relationship thereof shall also be regarded as the scope of the present invention without substantially changing the technical content.

[0042] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0043] The present invention will be further described below in conjunction with the following examples.

[0044] Example 1

[0045] The invention discloses an anti-aging rock asphalt composite modified asphalt, which comprises, by weight, 100 parts of base asphalt, 12 parts of Iranian rock asphalt, 10 parts of asphalt modification additive, 3 parts of aromatic oil substances and 2 parts of plasticizer.

[0046] The base asphalt is 90# base asphalt. The asphalt content of Iranian rock asphalt is ≥80wt%, ash content is ≤20wt%, water content is ≤1wt%, trichloroethylene solubility is ≥84wt%, and density is 0.90-0.97g / cm 3 (25℃), black in color, particle size is 100 mesh. Aromatic oil is furfural extracted oil, density is 1.02g / cm 3 (15.6℃), kinematic viscosity is 42.6mm 2 / s (100°C), the total aromatic content is 82.8wt%. The plasticizer is dioctyl phthalate (DOP).

[0047] The preparation method of the asphalt modification additive comprises:

[0048] S1. Treatment of zirconium disilicide:

[0049] The invention relates to a method for preparing zirconium disilicide nanopowder of 200-300 nm and γ-glycidyloxypropyltrimethoxysilane, and mixing the mixture into anhydrous ethanol. The mixture is ultrasonicated at room temperature until the mixture is uniform. Acetic acid is then added dropwise to adjust the pH value to 4-5. The mixture is heated to 45° C. and stirred for 12 hours. After the reaction is completed, the powder is filtered out, washed with water for at least three times, and dried at 80° C. to obtain epoxidized zirconium disilicide powder. The mass ratio of the zirconium disilicide nanopowder, γ-glycidyloxypropyltrimethoxysilane and anhydrous ethanol is 1:0.3:15.

[0050] S2. Preparation of silicone rubber:

[0051] Vinyl silicone oil, 1-ethynyl-1-cyclohexanol, hydrogenated silicone oil and Karstedt catalyst are added to a mixing device in sequence, and after a short period of high-speed stirring, i.e., stirring at a speed of 800 rpm for 3 minutes, ammonium carbonate powder with a particle size of 5±0.1 μm is added, and the added amount is 5% of the mass of the vinyl silicone oil, and then stirred at a speed of 1100 rpm for 4 minutes, placed in a mold and allowed to stand for 10 minutes, and then placed in a 70° C. condition for 20 minutes, and then placed in a 135° C. condition for 30 minutes, and after natural cooling, crushed through a 50-mesh sieve to obtain porous silicone rubber particles; the mass ratio of vinyl silicone oil, 1-ethynyl-1-cyclohexanol, hydrogenated silicone oil and Karstedt catalyst is 26.4:1.91:0.5:1.2.

[0052] S3, Silicone rubber pretreatment:

[0053] The porous silicone rubber particles were immersed in a 50% ethanol solution. After all the particles were soaked, γ-aminopropyltriethoxysilane was added and stirred at room temperature for 4 hours. The particles were then filtered, washed with water for at least three times, and dried at 80°C to obtain a silicone rubber pretreatment product. The mass ratio of γ-aminopropyltriethoxysilane, porous silicone rubber particles and ethanol solution was 3.5:12:100.

[0054] S4. Preparation of modified silicone rubber:

[0055] The silicone rubber pretreatment material and epoxidized zirconium disilicide powder were mixed into toluene, ultrasonically homogenized, swelled for half an hour, then heated to 65°C, refluxed with stirring for 4 hours, filtered and dried to obtain modified silicone rubber; the mass ratio of the silicone rubber pretreatment material, epoxidized zirconium disilicide powder and toluene was 1:0.18:15.

[0056] The preparation method of the composite modified asphalt comprises:

[0057] First, the Iranian rock asphalt is crushed and sieved with a 50-mesh sieve to obtain a sufficient amount of Iranian rock asphalt;

[0058] Secondly, 3 parts of furfural extracted oil and 2 parts of plasticizer DOP were weighed and stirred rapidly for 4 min with a glass rod, and the mixture was divided into group A and group B according to a mass ratio of 3:1;

[0059] Then, 12 parts of the sieved Iranian rock asphalt and 10 parts of the asphalt modification additive were weighed, and the mixture was quickly stirred and mixed with group A using a glass rod for 4 minutes, and then placed in an oven at 80°C for curing for 24 hours; after the curing was completed, 100 parts of 90# matrix asphalt were added to the Iranian rock asphalt mixture, and high-speed shearing was performed in an oil bath at 165°C for 45 minutes, wherein the shear rate was set to 5000 m / min;

[0060] Finally, after the high-speed shearing is completed, the high-speed shearing equipment is replaced with a mechanical stirring equipment, and the mixture of group B is added to the mixture obtained by high-speed shearing, and stirred and developed in an oil bath at 165°C for 10 minutes, wherein the stirring rate equipment is 600r / min. After the development, Iranian rock asphalt blended with aromatic oil and plasticizer composite modified asphalt is obtained.

[0061] Example 2

[0062] The invention discloses an anti-aging rock asphalt composite modified asphalt, which comprises, by weight, 100 parts of base asphalt, 5 parts of Iranian rock asphalt, 15 parts of asphalt modification additives, 2 parts of aromatic oil substances and 1 part of plasticizer.

[0063] The base asphalt is 90# base asphalt. The asphalt content of Iranian rock asphalt is ≥80wt%, ash content is ≤20wt%, water content is ≤1wt%, trichloroethylene solubility is ≥84wt%, and density is 0.90-0.97g / cm 3 (25℃), black in color, particle size is 100 mesh. Aromatic oil is furfural extracted oil, density is 1.02g / cm 3 (15.6℃), kinematic viscosity is 42.6mm 2 / s (100°C), the total aromatic content is 82.8wt%. The plasticizer is dioctyl maleate (DOM).

[0064] The preparation method of the asphalt modification additive is the same as that in Example 1.

[0065] The preparation method of the composite modified asphalt comprises:

[0066] First, the Iranian rock asphalt is crushed and sieved with a 50-mesh sieve to obtain a sufficient amount of Iranian rock asphalt;

[0067] Secondly, 2 parts of furfural extracted oil and 1 part of plasticizer DOM were weighed and stirred rapidly with a glass rod for 3 min. The mixture was divided into two parts according to the mass ratio of 3:1, marked as group A (3 parts) and group B (1 part);

[0068] Then, 5 parts of the sieved Iranian rock asphalt and 15 parts of the asphalt modification additive were weighed, and the mixture was quickly stirred and mixed with group A for 3 minutes using a glass rod, and then placed in an oven at 80°C for curing for 24 hours; after the curing was completed, 100 parts of 90# matrix asphalt were added to the Iranian rock asphalt mixture, and high-speed shearing was performed in an oil bath at 165°C for 45 minutes, wherein the shear rate was set to 4000 m / min;

[0069] Finally, after the high-speed shearing is completed, the high-speed shearing equipment is replaced with a mechanical stirring equipment, and the mixture of group B is added to the mixture obtained by high-speed shearing, and stirred and developed in an oil bath at 165°C for 10 minutes, wherein the stirring rate equipment is 500r / min. After the development, Iranian rock asphalt blended with aromatic oil and plasticizer composite modified asphalt is obtained.

[0070] Example 3

[0071] The invention discloses an anti-aging rock asphalt composite modified asphalt, which comprises, by weight, 100 parts of base asphalt, 20 parts of Iranian rock asphalt, 8 parts of asphalt modification additive, 4 parts of aromatic oil substances and 3 parts of plasticizer.

[0072] The base asphalt is 90# base asphalt. The asphalt content of Iranian rock asphalt is ≥80wt%, ash content is ≤20wt%, water content is ≤1wt%, trichloroethylene solubility is ≥84wt%, and density is 0.90-0.97g / cm 3 (25℃), black in color, particle size is 100 mesh. Aromatic oil is furfural extracted oil, density is 1.02g / cm 3 (15.6℃), kinematic viscosity is 42.6mm 2 / s (100°C), the total aromatic content is 82.8wt%. The plasticizer is tri-n-butyl citrate (TBC).

[0073] The preparation method of the asphalt modification additive is the same as that in Example 1.

[0074] The preparation method of the composite modified asphalt comprises:

[0075] First, the Iranian rock asphalt is crushed and sieved with a 50-mesh sieve to obtain a sufficient amount of Iranian rock asphalt;

[0076] Secondly, 4 parts of furfural extracted oil and 3 parts of plasticizer TBC were weighed and stirred rapidly with a glass rod for 5 min. The mixture was divided into two parts according to the mass ratio of 3:1, marked as group A and group B;

[0077] Then, 20 parts of the sieved Iranian rock asphalt and 8 parts of the asphalt modification additive were weighed, and the mixture was quickly stirred and mixed with group A for 5 minutes using a glass rod, and then placed in an oven at 80°C for curing for 24 hours; after the curing, 100 parts of 90# matrix asphalt were added to the Iranian rock asphalt mixture, and high-speed shearing was performed in an oil bath at 165°C for 45 minutes, wherein the shear rate was set to 4000 m / min;

[0078] Finally, after the high-speed shearing is completed, the high-speed shearing equipment is replaced with a mechanical stirring equipment, and the mixture of group B is added to the mixture obtained by high-speed shearing, and stirred and developed in an oil bath at 165°C for 10 minutes, wherein the stirring rate equipment is 700r / min. After the development, Iranian rock asphalt blended with aromatic oil and plasticizer composite modified asphalt is obtained.

[0079] Example 4

[0080] An anti-aging rock asphalt composite modified asphalt, which is different from Example 1 in that the base asphalt is 70# base asphalt and the preparation method of the asphalt modified additive is different. The preparation method of the asphalt modified additive includes:

[0081] S1. Treatment of zirconium disilicide:

[0082] Weigh 200-300nm zirconium disilicide nanopowder and γ-glycidyloxypropyltrimethoxysilane and mix them in anhydrous ethanol, perform ultrasonication at room temperature until uniform, then drop acetic acid to adjust the pH to 4-5, raise the temperature to 40°C, keep stirring for 8 hours, filter out the powder after the reaction, wash with water for at least three times, and dry at 80°C to obtain epoxidized zirconium disilicide powder; the mass ratio of the zirconium disilicide nanopowder, γ-glycidyloxypropyltrimethoxysilane and anhydrous ethanol is 1:0.25:10.

[0083] S2. Preparation of silicone rubber:

[0084] Vinyl silicone oil, 1-ethynyl-1-cyclohexanol, hydrogenated silicone oil and Karstedt catalyst are added to a mixing device in sequence, and after a short period of high-speed stirring, i.e., stirring at a speed of 700 rpm for 2 minutes, ammonium carbonate powder with a particle size of 5±0.1 μm is added, and the added amount is 3% of the mass of the vinyl silicone oil, and then stirred at a speed of 1000 rpm for 3 minutes, placed in a mold and allowed to stand for 10 minutes, and then placed in a 60° C. condition for 20 minutes, and then placed in a 130° C. condition for 30 minutes, and after natural cooling, crushed through a 50-mesh sieve to obtain porous silicone rubber particles; the mass ratio of vinyl silicone oil, 1-ethynyl-1-cyclohexanol, hydrogenated silicone oil and Karstedt catalyst is 21.1:1.53:0.4:0.96.

[0085] S3, Silicone rubber pretreatment:

[0086] The porous silicone rubber particles were immersed in a 50% ethanol solution. After all the particles were soaked, γ-aminopropyltriethoxysilane was added and stirred at room temperature for 3 hours. The particles were then filtered, washed with water for at least three times, and dried at 80°C to obtain a silicone rubber pretreatment product. The mass ratio of γ-aminopropyltriethoxysilane, porous silicone rubber particles and ethanol solution was 2.5:10:100.

[0087] S4. Preparation of modified silicone rubber:

[0088] The silicone rubber pretreatment material and epoxidized zirconium disilicide powder are mixed into toluene, ultrasonically homogenized, swelled for half an hour, then heated to 60°C, refluxed with stirring for 3 hours, filtered and dried to obtain modified silicone rubber; the mass ratio of the silicone rubber pretreatment material, epoxidized zirconium disilicide powder and toluene is 1:0.12:10.

[0089] The preparation method of the rock asphalt composite modified asphalt in this embodiment is the same as that in Example 1.

[0090] Example 5

[0091] An anti-aging rock asphalt composite modified asphalt, which is different from Example 1 in that the base asphalt is 70# base asphalt and the preparation method of the asphalt modified additive is different. The preparation method of the asphalt modified additive includes:

[0092] S1. Treatment of zirconium disilicide:

[0093] Weigh 200-300nm zirconium disilicide nanopowder and γ-glycidyloxypropyltrimethoxysilane and mix them in anhydrous ethanol, perform ultrasonication at room temperature until uniform, then add acetic acid dropwise to adjust the pH to 4-5, raise the temperature to 50°C, keep stirring for 16 hours, filter out the powder after the reaction, wash with water for at least three times, and dry at 80°C to obtain epoxidized zirconium disilicide powder; the mass ratio of the zirconium disilicide nanopowder, γ-glycidyloxypropyltrimethoxysilane and anhydrous ethanol is 1:0.35:20.

[0094] S2. Preparation of silicone rubber:

[0095] Vinyl silicone oil, 1-ethynyl-1-cyclohexanol, hydrogenated silicone oil and Karstedt catalyst are added to a mixing device in sequence, and after a short period of high-speed stirring, i.e., stirring at a speed of 900 rpm for 3 minutes, ammonium carbonate powder with a particle size of 5±0.1 μm is added, and the added amount is 8% of the mass of the vinyl silicone oil, and then stirred at a speed of 1200 rpm for 5 minutes, placed in a mold and allowed to stand for 10 minutes, and then placed in a treatment condition of 80° C. for 20 minutes, and then placed in a treatment condition of 140° C. for 30 minutes, after natural cooling, crushed through a 50-mesh sieve to obtain porous silicone rubber particles; the mass ratio of vinyl silicone oil, 1-ethynyl-1-cyclohexanol, hydrogenated silicone oil and Karstedt catalyst is 27.9:2.03:0.6:1.27.

[0096] S3, Silicone rubber pretreatment:

[0097] The porous silicone rubber particles were immersed in a 50% ethanol solution. After all the particles were soaked, γ-aminopropyltriethoxysilane was added and stirred at room temperature for 6 hours. The particles were then filtered, washed with water for at least three times, and dried at 80°C to obtain a silicone rubber pretreatment product. The mass ratio of γ-aminopropyltriethoxysilane, porous silicone rubber particles and ethanol solution was 4.5:15:100.

[0098] S4. Preparation of modified silicone rubber:

[0099] The silicone rubber pretreatment material and the epoxidized zirconium disilicide powder were mixed into toluene, ultrasonically homogenized, swelled for half an hour, then heated to 70°C, refluxed with stirring for 5 hours, filtered and dried to obtain modified silicone rubber; the mass ratio of the silicone rubber pretreatment material, the epoxidized zirconium disilicide powder and toluene was 1:0.24:20.

[0100] The preparation method of the rock asphalt composite modified asphalt in this embodiment is the same as that in Example 1.

[0101] Comparative Example 1

[0102] An anti-aging rock asphalt composite modified asphalt, which differs from Example 1 in that an equal amount of asphalt modification additive is replaced by zirconium disilicide powder.

[0103] Comparative Example 2

[0104] An anti-aging rock asphalt composite modified asphalt, which differs from Example 1 in that an equal amount of the asphalt modification additive is replaced by porous silicone rubber particles (prepared in the same manner as in Example 1).

[0105] Comparative Example 3

[0106] An anti-aging rock asphalt composite modified asphalt, the difference from Example 1 is that the preparation process of the asphalt modification additive is different. In this comparative example, zirconium disilicide is directly added during the synthesis of silicone rubber, specifically:

[0107] Vinyl silicone oil, 1-ethynyl-1-cyclohexanol, hydrogenated silicone oil and Karstedt catalyst are added to a mixing device in sequence, and after a short period of high-speed stirring, that is, stirring at a speed of 800 rpm for 3 minutes, zirconium disilicide powder with a particle size of 200-300 nm is added, and then stirred at a speed of 1100 rpm for 4 minutes, placed in a mold for 10 minutes, and then placed in a 70° C. condition for 20 minutes, and then placed in a 135° C. condition for 30 minutes, and after natural cooling, crushed through a 50-mesh sieve to obtain porous silicone rubber particles; the mass ratio of vinyl silicone oil, 1-ethynyl-1-cyclohexanol, hydrogenated silicone oil and Karstedt catalyst is 26.4:1.91:0.5:1.2, and the mass ratio of the total mass of vinyl silicone oil, 1-ethynyl-1-cyclohexanol, hydrogenated silicone oil and Karstedt catalyst to the mass ratio of zirconium disilicide nanopowder is 1:0.18.

[0108] The modified asphalt obtained in Example 1 and Comparative Examples 1-3 is subjected to aging resistance and high and low temperature resistance performance tests, including softening point, freeze-thaw splitting test residual strength ratio, ductility and dynamic stability; at the same time, the modified asphalt is aged for 36 hours in a UV aging oven and compared with the original sample. The detection standard refers to the "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011). The experimental results are shown in Appendix 1.

[0109] Table 1 Performance indexes of rock asphalt composite modified asphalt

[0110]

[0111] The results in Table 1 show that the rock asphalt composite modified asphalt of Example 1 of the present invention has excellent high and low temperature performance of modified asphalt, and the strength and high and low temperature performance change degree after aging is small. Therefore, the rock asphalt composite modified asphalt prepared by the present invention has excellent strength, high and low temperature performance and anti-aging performance.

[0112] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms should not be understood as necessarily being directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.

[0113] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. An anti-aging rock asphalt composite modified asphalt, characterized in that: Calculated by weight, it includes: 100 parts of base asphalt, 5-20 parts of Iranian rock asphalt, 8-15 parts of asphalt modification additives, 2-4 parts of aromatic oil substances and 1-3 parts of plasticizer; Wherein, the matrix asphalt is any one of 70# and 90# matrix asphalt, and the asphalt modification additive is modified silicone rubber; The preparation method of the modified silicone rubber comprises: S1. Treatment of zirconium disilicide: Weighing zirconium disilicide nanopowder and γ-glycidyloxypropyltrimethoxysilane, mixing them into anhydrous ethanol, ultrasonicating them at room temperature until they are uniform, then dropping acetic acid to adjust the pH to 4-5, raising the temperature to 40-50° C., keeping the temperature and stirring for 8-16 hours, after the reaction is completed, filtering out the powder, washing with water for at least three times, and drying at 80° C. to obtain epoxidized zirconium disilicide powder; S2. Preparation of silicone rubber: Vinyl silicone oil, 1-ethynyl-1-cyclohexanol, hydrogenated silicone oil and Karstedt catalyst are added to the mixing device in sequence, and after a short period of high-speed stirring, i.e., stirring at a speed of 700-900 rpm for 2-3 minutes, ammonium carbonate powder is added, and then stirred at a speed of 1000-1200 rpm for 3-5 minutes, placed in a mold and allowed to stand for 10 minutes, and then placed in a condition of 60-80°C for 20 minutes, and then placed in a condition of 130-140°C for 30 minutes, and then naturally cooled, crushed and sieved to obtain porous silicone rubber particles; S3, Silicone rubber pretreatment: The porous silicone rubber particles are immersed in an ethanol solution, and after being completely soaked, γ-aminopropyltriethoxysilane is added, and the mixture is stirred at room temperature for 3-6 hours, and then filtered, washed with water for at least three times, and dried at 80° C. to obtain a silicone rubber pretreatment product; S4. Preparation of modified silicone rubber: The silicone rubber pretreatment product and the epoxidized zirconium disilicide powder are mixed into toluene, ultrasonically homogenized, swelled for half an hour, then heated to 60-70°C, refluxed and stirred for 3-5 hours, filtered and dried to obtain the modified silicone rubber.

2. The anti-aging rock asphalt composite modified asphalt according to claim 1, characterized in that: The asphalt content of the Iranian rock asphalt is ≥80wt%, the ash content is ≤20wt%, the water content is ≤1wt%, the solubility of trichloroethylene is ≥84wt%, and the density at 25°C is 0.90-0.97g / cm 3 , color is black, particle size is 100 mesh.

3. The anti-aging rock asphalt composite modified asphalt according to claim 1, characterized in that: The aromatic oil substance is furfural extracted oil, and the density at 15.6°C is 1.02 g / cm 3 , the kinematic viscosity at 100°C is 42.6 mm 2 / s, and the total aromatic content is 82.8wt%.

4. The anti-aging rock asphalt composite modified asphalt according to claim 1, characterized in that: The plasticizer is any one of dioctyl phthalate, dioctyl maleate, tri-n-butyl citrate and composite plant fatty acid.

5. The anti-aging rock asphalt composite modified asphalt according to claim 1, characterized in that: In the S1, the mass ratio of the zirconium disilicide nanopowder, γ-glycidyloxypropyltrimethoxysilane and anhydrous ethanol is 1:0.25-0.35:10-20.

6. The anti-aging rock asphalt composite modified asphalt according to claim 1, characterized in that: In S2, the vinyl silicone oil is RH-Vi302 or RH-Vi303, and the hydrogen-containing silicone oil is MHX-1107; the mass ratio of vinyl silicone oil, 1-ethynyl-1-cyclohexanol, hydrogen-containing silicone oil and Karstedt catalyst is 21.1-27.9:1.53-2.03:0.4-0.6:0.96-1.

27.

7. The anti-aging rock asphalt composite modified asphalt according to claim 1, characterized in that: The amount of ammonium carbonate powder added is 3%-8% of the mass of the vinyl silicone oil.

8. The anti-aging rock asphalt composite modified asphalt according to claim 1, characterized in that: In S3, the mass fraction of the ethanol solution is 50%, and the mass ratio of γ-aminopropyltriethoxysilane, porous silicone rubber particles and the ethanol solution is 2.5-4.5:10-15:

100.

9. The anti-aging rock asphalt composite modified asphalt according to claim 1, characterized in that: In the S4, the mass ratio of the silicone rubber pretreatment material, the epoxidized zirconium disilicide powder and toluene is 1:0.12-0.24:10-20.

10. A method for preparing the anti-aging rock asphalt composite modified asphalt according to claim 1, characterized in that: The steps include: Step 1: crush the Iranian rock asphalt and sieve it with a 50-mesh sieve; Step 2: Weigh the aromatic oil substance and the plasticizer according to weight, stir evenly, and then divide the mixture into group A and group B according to a weight ratio of 3:1; Step 3: Weigh the Iranian rock asphalt and asphalt modification additive according to the mass ratio, mix them with Group A in Step 2, stir them quickly and evenly, and then put them into an oven for curing; Step 4: Place the base asphalt in an oven, heat it to fluidity, weigh the base asphalt according to the mass ratio, and perform high-speed shearing with the cured Iranian rock asphalt mixture; Step 5: Replace the high-speed shearing equipment in step 4 with a mechanical stirring equipment, add group B in step 2 into the mixture obtained in step 4, and stir and develop it. After the development is completed, a composite modified asphalt can be obtained.

Citation Information

Patent Citations

  • One-component addition type liquid silicone rubber and preparation method thereof

    CN105238070A

  • High-performance anti-rutting modified asphalt

    CN106147256A